Система интегральных уравнений первого рода на отрезке [0,2π ] с логарифмическим ядром - Полянская, Татьяна Семеновна (НТУ "ХПИ", 2015)
Рассмотрена система интегральных уравнений первого рода с логарифмическим ядром, к которой приводит ряд задач дифракции волн. Проведена дискретизация этой системы на основе метода дискретных особенностей. Введены пары гильбертовых пространств и операторы, в них, соответствующие заданной и дискретной задачам. С их помощью доказана однозначная разрешимость дискретной задачи и дано строгое обоснование оценки скорости сходимости решения дискретной задачи к точному решению системы интегральных уравнений.

A system of integral equations of the first kind with logarithmic kernel, which arises in a number of problems of the diffraction of waves, is studied. The sampling of the system is obtained by the method of discrete singularities. Pairs of Hilbert spaces and operators in them, corresponding to the set and discrete problems are introduced. Using them we prove the unique solvability of the discrete problem and provide a rigorous justification for estimating the rate of convergence of the solution of the discrete problem to the exact solution of the integral equations.
A system of integral equations of the first kind with a logarithmic kernel on [0, 2π ]
Keywords: метод дискретных особенностей; квадратурные формулы; вектор-функции; гильбертово пространство; integral equations; logarithmic kernel; method of discrete singularities